THE USE OF CANVA-BASED INTERACTIVE LEARNING MEDIA TO IMPROVE LEARNING OUTCOMES IN SCIENCE FOR JUNIOR HIGH SCHOOL STUDENTS - sasmia; Mareta Widiya (Teaching and General Education Studies, 2026)
This study aims to determine the feasibility of using Canva-based interactive learning media in science subjects for junior high school students. The problem addressed in this study is the decline in students’ understanding, motivation, and interest in learning, which leads to low learning outcomes. Therefore, innovation in the learning process is needed through the use of interactive learning media based on Canva. This study employed a descriptive qualitative method using a literature study technique by reviewing five relevant journals. The results show that Canva-based interactive learning media increases students’ motivation, learning interest, and learning outcomes. The media is proven to be valid, practical, and effective in enhancing student engagement and facilitating understanding.